Violation of cells energy supply as one of the mechanisms of combined trauma of the chest and both thighs in rats and ways of its correction - Marushchak, Maria; Khudobiak, Maksym; Antonyshyn, Iryna; Mialiuk, Oksana (Journal of Education, Health and Sport, 2017)
UDC 612.017.1-02:616-001.316-036.8-085.275.14]-092.9 The trauma of the chest is one of the most serious chest injuries and also causes of mortality in 25% of cases, giving way mortality from head injuries and spinal cord [4, 5]. It should be noted that data of the scientific literature indicates a high frequency of combined injuries of the chest and limbs, which ranges from 3.4 to 11.7% [6]. The high morbidity and mortality in polytrauma necessitates a deeper study of the mechanisms and the flow of post-traumatic period. The aim of our work was to evaluate indicators of mitochondrial system electron transport in the tissues of the heart, lungs and liver in dynamics after transferred combined trauma of the chest and both thighs and in the case of correction by derivatives of 3-oxypyridine. Post-traumatic period of combined trauma of the chest and both thighs in rats characterized by disorganization power supplying oxidation with maximum energy deficit in the lungs by 3-7 days (reducing the activity of succinate dehydrogenase and cytochrome oxidase by an average of 36.5%), after 3 days - in the heart (accordingly by 38.6% and 47.7%) and liver (accordingly by 19.5% and 23.7%). The use of derivatives of 3-oxypyridine in the case of experimental combined trauma of the chest and both thighs statistically significantly intensify energy synthesizing mitochondrial function, and the effect of 2-ethyl-6-methyl-3- hydroxypyridine succinate (mexicor) the activity of succinate dehydrogenase is expressive, concerning the effects of 3 -oxy-6-methyl-2- ethylpyridine hydrochloride (emoxypine), in the heart for 3-14 days and in the liver after 7 and 14 days of observation (p≤0,05).